Great answers, great questions for your job interview - Block, Jay A. (McGraw-Hill Education, 2014)
This is the classic guide to acing any interview-updated with critical skills for networking, video interviewing, and researching companies. Great Answers, Great Questions For Your Job Interview prepares you to answer the trickiest questions and make yourself stand out from the competition. From pre-interview research to follow-up calls, the authors walk you through every step of the process and provide powerful advice on customizing your resume for any position. Includes worksheets and exercises that help you practice your responses to interview questions new: how to land an interview through smart networking, researching a company before the interview, and following up afterwards on LinkedIn and other social media sites; new: preparing for a video interview on Skype; new: tips on salary negotiation; new: techniques for creating a "culture match" with a potential employer; and new: essential information on role playing. Jay A. Block is the cofounder of the Professional Association of Resume Writers and Career Coaches (PARW/CC). He developed a groundbreaking career management and empowerment program for the Workforce Development System nationwide, the U.S. Department of Labor, and other leading career and employment-related organizations. Michael Betrus is a sales director by trade, having conducted hundreds of interviews and hires, and a career seminar leader for students on campuses nationwide